Analysis of Economic Growth During the Crisis in Indonesia - Rahma, Taufiqah; Azhar, Zul (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
The COVID-19 pandemic has had a broad and profound impact on various sectors of life, including the economy. This research aims to analyze how economic growth affects the open unemployment rate, consumption, and investment in Indonesia during the COVID-19 pandemic. Secondary data from official sources, such as the Central Statistics Agency, Bank Indonesia, and Food and Agriculture Organization reports, were analyzed using a quantitative approach. The regression method was applied to identify the relationship between economic growth, unemployment rate, consumption, and investment before and during the pandemic. The research results indicate that the decline in economic growth during the pandemic significantly impacted the increase in the open unemployment rate, the decrease in household consumption, and the reduction in investment levels. These findings emphasize the need for policies that are more responsive and focused on economic recovery, particularly in creating jobs, increasing people's purchasing power, and encouraging sustainable investment. It is hoped that the implications of this research will provide guidance for policymakers in designing more effective post-pandemic economic recovery strategies.